Intrinsic determinants of Aβ(12-24) pH-dependent self-assembly revealed by combined computational and experimental studies. - Weixin Xu (Public Library of Science (PLoS), 2011)
The propensity of amyloid-β (Aβ) peptide to self-assemble into highly ordered amyloid structures lies at the core of their accumulation in the brain during Alzheimer's disease. By using all-atom explicit solvent replica exchange molecular dynamics simulations, we elucidated at the atomic level the intrinsic determinants of the pH-dependent dimerization of the central hydrophobic segment Aβ(12-24) and related these with the propensity to form amyloid fibrils measured by experimental tools such as atomic force microscopy and fluorescence. The process of Aβ(12-24) dimerization was evaluated in terms of free energy landscape, side-chain two-dimensional contact probability maps, β-sheet registries, potential mean force as a function of inter-chain distances, secondary structure development and radial solvation distributions. We showed that dimerization is a key event in Aβ(12-24) amyloid formation; it is highly prompted in the order of pH 5.0>2.9>>8.4 and determines further amyloid growth. The dimerization is governed by a dynamic interplay of hydrophobic, electrostatic and solvation interactions permitting some variability of β-sheets at each pH. These results provide atomistic insight into the complex process of molecular recognition detrimental for amyloid growth and pave the way for better understanding of the molecular basis of amyloid diseases.